The Third International Conference on the Development of Biomedical Engineering in Vietnam c - Toi, Vo.; Khoa, Truong Quang Dang.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The Third International Conference on the Development of Biomedical Engineering in Vietnam was organized on January 11-14, 2010, by IU in Ho Chi Minh City, Vietnam and had the theme of: (3z(BNew frontiers in Biomedical Engineering(3y(B. It reflected the steady growth of the activities in this field in Vietnam, and featured the contributions of researchers of 21 countries, including: Australia, Belgium, Canada, Denmark, France, India, Japan, Korea, Malaysia, New Zealand, Philippines, Poland, Russia, Singapore, Spain, Switzerland, Taiwan, Thailand, United Kingdom, the United States and Vietnam. Besides the invited, oral and poster presentations there were tutorial lectures to educate junior researchers in different subfields of Biomedical Engineering. This volume summarizes those presentations and was provided as an education foundation and scientific reference.s
Keynote Speakers -- Invited Speakers -- Modeling -- Instrumentation -- Molecular/Cell -- Imaging -- Biomaterial -- Educational Model -- Others -- Lab-On-A- Chip - Applied Micro and Nanotechology in Life Sciences.
Keywords: Engineering; Biomedical engineering; Biomaterials; Engineering; Biomedical Engineering; Biomaterials; Biophysics and Biological Physics